Multinational strategy: an overview - Tallman, Stephen (Henry Stewart Talks, 2013)
Multinational strategy, Value proposition, Asset management, Location and context, Multinational strategy processes, Globalization drivers, International distance, Competitive and industry analysis, Integration & responsiveness, Resources and capabilities of multinational firms, Capability strategies, International generic strategies, Market entry strategies, International acquisitions, International alliances and joint ventures